Cognitive strategies and the use of prior knowledge in learning - Christine H. Olgren (Adult Education Research Conference, 1993)
This study investigated adults' cognitive processes in learning from text and factors influencing cognition. Identified were three groups of learners who differed in cognitive strategies, motivation, and use of prior domain knowledge.